Adnexal torsion clinical characteristics and treatment: 17 years experience - Carrasco, Amparo (2016)
Objectives: To present the descriptive epidemiology in a group of women with adnexal torsion. Design: Observational, descriptive and retrospective study. Setting: Hospital Universitario Doctor Peset, Valencia. Spain. Participants: Women diagnosed of adnexal torsion. Interventions: Between February 1997 and June 2014, 54 patients 11-64 years old with adnexal torsion were included. Results: The mean onset age was 31.7 years old. Previous adnexal surgery was reported in 6 cases (11.1%). The right adnexal region was the most affected; 34 (62.9%) patients were adnexal mass carriers. The most common presenting symptom was acute pelvic pain, and the mean lag time between onset of symptoms and confirmation of diagnosis was 24-72 hours. Fourteen (25.9%) patients were treated by laparotomy and 40 (74.1%) by laparoscopy. Recurrence occurred in 3 patients (5.6%). Conclusions: Adnexal torsion should be considered in every woman complaining of pelvic pain in emergency services. A prompt surgical intervention is required to avoid irreversible ovarian damage. Nowadays, conservative therapy by laparoscopy is preferred in these patients.